Time-dependent behaviour of circular steel tube confined reinforced concrete (STCRC) slender columns. (1st June 2023) - Guo, Yun-Long; Geng, Yue; Liew, J.Y. Richard; Ma, Huan-chi; Wang, Yu-Yin
Highlights: Long-term vertical stiffness contribution of tube in slender STCRC columns. Time-dependent confinement effects in slender STCRC columns. Time varying coupling influence of confining and longitudinal interfacial effects. Prediction method for the long-term responses of slender STCRC columns. Abstract: Steel tube confined reinforced concrete (STCRC) columns are usually used as key structural elements in long-span and high-rise structures with high load resistance and outstanding seismic behaviour. To date, no investigation has been conducted on the long-term behaviour of slender STCRC columns. In this context, the long-term tests on axially loaded slender STCRC columns were firstly presented with various slenderness ratios and grades of concrete. The distributions of the tube's circumferential and vertical stresses along the length of the column were carefully monitored throughout the tests to investigate the time-dependent tube stiffness contribution and their coupling effects with the confining pressure. By considering these two factors, a reliable analysis method was proposed and validated by the available test results. It was shown that, within the test parameters in this paper, the steel tube can contribute up to 12.6 % of axial stiffness of the composite columns, which is different from that predicted based on plane section assumption. The tube stiffness contribution increased with time and was more pronounced in columns with higher slenderness ratio or lower concrete strength. The coupling effects between the vertical stress and the confining pressure were not negligible for slender STCRC columns. The proposed method showed good accuracy in predicting long-term responses with errors less than +6.4 % and −2.9 %.